2015
DOI: 10.1097/njh.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues Experienced by Hospice and Palliative Nurses

Abstract: Nurses encounter ethical dilemmas in their clinical practice especially those associated with palliative and end-of-life care. The Hospice and Palliative Nurses Association (HPNA) members were asked to participate in an ethics survey. The survey aimed to identify ethical issues experienced by hospice and palliative nurses, identify resources available to them and barriers if any to their use, and to identify how HPNA can be of support to hospice and palliative nurses. One hundred twenty-nine (n = 129) HPNA mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(63 citation statements)
references
References 12 publications
2
61
0
Order By: Relevance
“…It also covered whether it may be appropriate to withhold information from patients, either because of clinician beliefs regarding harms, or the wish of the families. 13,15,38,39,42,[43][44][45][46][47] High confidence. This finding is contributed to by most of the studies included in the review.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It also covered whether it may be appropriate to withhold information from patients, either because of clinician beliefs regarding harms, or the wish of the families. 13,15,38,39,42,[43][44][45][46][47] High confidence. This finding is contributed to by most of the studies included in the review.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…Administration of antibiotics 15 Appropriate use of antibiotics, particularly in end of life care. Advance directives 13,40,45 Challenges implementing advance directives, particular when family requests may contrast with the directive. Bloods transfusions 15,44 Appropriateness of blood transfusions.…”
Section: Ethical Challenge Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…One research article (Speroni, Fitch, Dawson, Dugan, & Atherton, 2014) and one conference abstract (Pompeii, Schoenfisch, Lipscomb, Dement, & Upadhyaya, 2014) identified drug-seeking behavior as responsible for an increase in workplace violence in hospitals, with no definition or description of the term provided. A research article indicated that concern about drug-seeking behavior was a primary factor contributing to hospice and palliative care nurses' inability to resolve an ethical dilemma, with no elaboration (Cheon, Coyle, Wiegand, & Welsh, 2015), and a description of a medication on demand device used by postoperative cesarean patients indicated that a history of drug-seeking was a contraindication (Hreniuk, Sheaffer, Sukeena, & Tribioli, 2014). An abstract describing an educational simulation of a drug-seeking patient in an ED setting described the scenario as beginning with 'a soft-spoken patient whose request for intravenous morphine was not met and then is transformed into a loud, manipulative, and demanding patient' (Bauer, 2019, 274).…”
Section: Smentioning
confidence: 99%
“…Patient autonomy is consistent with what some would label an essential element of bioethical principles in Western hemisphere cultures but not across all cultural variations (Kara, 2007). Autonomy is a value that encompasses the freedom to make individual choices and decide on a course of action for those who are capable (Beauchamp & Childress, 2013;Cheon et al, 2015). The amount of autonomy is wholly governed by the patient and family acknowledging their cultural/religious preferences.…”
Section: Middle Circle Of Framework Guiding Interprofessional Valuesmentioning
confidence: 62%